2013
DOI: 10.4318/tjg.2013.0528
|View full text |Cite
|
Sign up to set email alerts
|

Increased bile lithogenicity by SCP2 via HMGCR and CYP7A1 regulation in human hepatocytes

Abstract: Girifl ve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…We found that levels of CYP7A1 were increased in patient fibroblasts compared to control cells, which is in line with a previous report citing CYP7A1 repression in SCP2 -overexpressing human hepatocytes (Fig. 3 C) [ 21 ].…”
Section: Resultssupporting
confidence: 93%
“…We found that levels of CYP7A1 were increased in patient fibroblasts compared to control cells, which is in line with a previous report citing CYP7A1 repression in SCP2 -overexpressing human hepatocytes (Fig. 3 C) [ 21 ].…”
Section: Resultssupporting
confidence: 93%